Rencana Tapak (Siteplan) sebagai Persyaratan Mutlak Penerbitan Persetujuan Bangunan Gedung (PBG) di Kabupaten Tangerang (Studi Kasus: Proses Permohonan Siteplan (Rencana Tapak) Lapangan Basket) - Arie Misbach; Mardi Aman (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The planning stage in project management is indispensable, where the planning contains technical and non-technical plans for a construction project to be executed (Executing). Planning has an important role so that the construction project will be carried out in accordance with the initiation set by the owner, and the building being built does not violate the rules set by the Regional Government at the location where the building will be erected. Site plan (Site plan) plays an important role in the planning stage. The site plan (Site plan) contains information regarding the direction of land use to be erected by the executor of the building construction. The information contained in the Site Plan includes: Percentage of land area that can be utilized for constructing buildings, Boundary Lines of Buildings to Roads, Building Height Limits, directions for providing Green Open Spaces (RTH) which function as water catchments, modeling of access in and out of land to be used. With the existence of a site plan, the building designed by the architect will be more organized in accordance with the applicable Tangerang Regency Spatial Planning Regulations. A site plan that has been approved by the Regional Government of Tangerang Regency is an important document and an absolute requirement for obtaining a Building Approval (PBG).